Corporate Governance and Tax Regimes in India - KUMAR, DR. P. PRAVEEN; KUMAR. G, MR. RAJ (The journal of contemporary issues in business and government, 2020)
This paper studies the perception towards essentials of corporate governance practices. Descriptive research is applied using a convenience method of sampling with 64 respondents. The data is collected from the private limited employees. The majority of respondents were Female and the majority of the age group were less than 35 years. The tools and techniques utilized for the examination and results are mean investigation, frequency test and ANOVA. It is discovered that there is no huge distinction between the perceptions towards essentials of corporate administration and the demographic profile of the employees.